Malondialdehyde and antioxidant content of pasteurized, semi-skimmed uht and uht milks - Filiz Kazak (Eurasian Journal of Veterinary Sciences)
Aim: In this study, to evaluate oxidant and antioxidant parameters of pasteurized, semi-skimmed UHT and UHT milks, the malondialdehyde (MDA), vitamin (Vit) C, total protein (TP), reduced glutathione (rGSH) levels and catalase (CAT) activity of them were determined and correlations between these parameters were revealed. Materials and Methods: Thirty milk samples from different trademarks were collected from different markets in Hatay. Milk MDA, Vit C, TP, rGSH levels and CAT activity were determined by spectrophotometric methods. Results: The lowest MDA level was determined in semi-skimmed UHT milk (p < 0.05). Pasteurized milk MDA level was higher than semi-skimmed UHT milk (p < 0.05). The levels of Vit C (p < 0.001) and TP (p < 0.01) in pasteurized milk were found to be higher than in the others. The rGSH levels of pasteurized and UHT milks were higher than semi-skimmed UHT milk (p < 0.05). UHT semiskimmed milk CAT activity (p < 0.05) was found to be quite high compared to other milks. As regards correlations; pasteurized milk MDA level was positively correlated with Vit C level (r = 0.743, p < 0.01). Semi-skimmed UHT milk TP level was positively correlated with CAT activity (r = 0.673, p < 0.05). Conclusion: As a result, the levels of oxidant (MDA), antioxidant parameters (Vit C, rGSH, and CAT), and TP in pasteurized, semi-skimmed UHT and UHT milk were evaluated and discussed in the present study. With this study, it is suggested that consumption of pasteurized milk may be healthier than semiskimmed UHT and UHT milks.